The need for educating healthcare professionals regarding good musculoskeletal health practice - Mohd Yusoff, Nurul Shazlina; Firdaus, Mohd Khairul Zul Hasymi; Che Jamaludin, Farrah Ilyani; Che Hasan, Muhammad Kamil (Elsevier, 2019)
Objective The objective of this study was to assess the level of knowledge and practice of body mechanics towards preserving musculoskeletal health in daily routine activities of HCPs (medical officers, staff nurses, community health nurses, assistant medical officers, physiotherapists, and assistant nurses) from Hospital Tengku Ampuan Afzan, Pahang.